The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s13054-016-1467-2
|View full text |Cite
|
Sign up to set email alerts
|

Should we treat pyrexia? And how do we do it?

Abstract: The concept of pyrexia as a protective physiological response to aid in host defence has been challenged with the awareness of the severe metabolic stress induced by pyrexia. The host response to pyrexia varies, however, according to the disease profile and severity and, as such, the management of pyrexia should differ; for example, temperature control is safe and effective in septic shock but remains controversial in sepsis. From the reported findings discussed in this review, treating pyrexia appears to be b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 63 publications
(105 reference statements)
1
40
0
4
Order By: Relevance
“…A 4 g day À1 dose is often administered as standard, but reports suggest this is frequently ineffective for fever control in patients with brain injury. 1 Other studies using a higher dose (6 g day À1 ) have shown small but important reductions in temperature. 1,18,19 Many of these studies administered paracetamol to all patients, not only those with fever, so it is difficult to draw firm conclusions on its use in fever.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A 4 g day À1 dose is often administered as standard, but reports suggest this is frequently ineffective for fever control in patients with brain injury. 1 Other studies using a higher dose (6 g day À1 ) have shown small but important reductions in temperature. 1,18,19 Many of these studies administered paracetamol to all patients, not only those with fever, so it is difficult to draw firm conclusions on its use in fever.…”
Section: Discussionmentioning
confidence: 96%
“…TTM has been used in several clinical situations, such as out-of-hospital cardiac arrest, traumatic brain injury (TBI), and cerebral vascular accidents, in an attempt to reduce neurological damage and enhance functional outcomes. 1 The evidence base for TTM use in patients with intracerebral haemorrhage (ICH), subarachnoid haemorrhage (SAH), or acute ischaemic stroke (AIS) is limited and difficult to interpret given the range of TTM methods used, the different target temperatures used, the heterogeneity of the patient groups, and the presence or absence of neurogenic or infectious fever. A similar amount of heterogeneity exists in the limited number of clinical guidelines published in France and the USA.…”
mentioning
confidence: 99%
“…Pyrexia, or fever, in contrast to hyperthermia, is defined as an elevated body temperature that occurs due to alteration of the thermoregulatory set point in the anterior hypothalamus in response to endogenous or exogenous pyrogens (Doyle & Schortgen ). Pyrexia is a highly conserved physiological adaptive response that, in the short term, confers an evolutionary advantage, particularly when combating infectious disease (Kluger et al .…”
Section: Introductionmentioning
confidence: 99%
“…Dabei ist bekannt, dass eine erhöhte Körpertemperatur bei bakteriellen Infektionen mit einem verbesserten Überleben einhergeht [17][18][19]. Dahingegen bleibt es unklar, ob die alleinige Senkung der Temperatur nicht auch gefährlich ist [20,21].…”
Section: Fieberunclassified